Complications of teenage pregnancy (Research, Society and Development, 2022)
Introduction: Adolescence comprises the period from 10 to 19 years of age. This change from childhood to adulthood is marked by several changes, whether physical, social, sexual and psychological. Objective: The present study sought to identify complications related to teenage pregnancy. Methodology: This is an integrative literature review article that aims to group and synthesize results of empirical research on the subject in question, with the following health descriptors: "Complications in pregnancy", "Pregnancy in Adolescence" and " Adolescence". They were searched in the Virtual Health Library (VHL), in the databases of Latin American Literature in Health Sciences (LILACS), (BDENF – NURSING) and COLECIONA (SUS). Inclusion criteria: Articles published between the years 2015 to 2020, Portuguese language, full text of free access and theme consistent with the research objective. Exclusion criteria: Duplicate articles in the databases, those that did not have affinity with the theme, incomplete and/or unavailable text. 10 articles were selected. Results: The studies showed that teenage pregnancy can lead to several complications and serious risks of morbidity and mortality for the binomial. For it is in this age group that the female reproductive system is undergoing a series of changes. Final considerations: It is important that these adolescents have knowledge about contraceptive methods, the prevention of sexually transmitted infections and are included in school through educational programs, in addition to the participation of parents in their children's sexual and reproductive education.